2016
DOI: 10.4077/cjp.2016.bae406
|View full text |Cite
|
Sign up to set email alerts
|

Performance Trends in Age Group Breaststroke Swimmers in the FINA World Championships 1986-2014

Abstract: Performance trends in breaststroke swimmers competing at world class level in pool competitions are well investigated for elite swimmers, but not for age group swimmers. This study investigated trends in participation, performance and sex difference in performance in a total of 35,143 (16,160 women and 18,983 men) age group breaststroke swimmers aged 25-29 to 95-99 years competing in the Fédération Internationale de Natation (FINA) World Masters Championships between 1986 and 2014. Trends in participation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…This confirms previous findings for other master athletes such as master marathon runners (Lepers and Cattagni, 2012) and master swimmers (Akkari et al, 2015; Medic et al, 2009). Also in freestyle (Knechtle et al, 2016a), backstroke (Unterweger et al, 2016) and breaststroke (Knechtle et al, 2016b), female and male master swimmers improved race times across years in all age groups and distances. However, this study shows that also octogenarians and nonagenarians improved their performance in swimming, since in the studies of Akkari et al (2015) and Lepers and Cattagni (2012), the oldest athletes were younger than 80 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms previous findings for other master athletes such as master marathon runners (Lepers and Cattagni, 2012) and master swimmers (Akkari et al, 2015; Medic et al, 2009). Also in freestyle (Knechtle et al, 2016a), backstroke (Unterweger et al, 2016) and breaststroke (Knechtle et al, 2016b), female and male master swimmers improved race times across years in all age groups and distances. However, this study shows that also octogenarians and nonagenarians improved their performance in swimming, since in the studies of Akkari et al (2015) and Lepers and Cattagni (2012), the oldest athletes were younger than 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…For backstroke swimmers, there was no consistent trend in the men-to-women ratio (Unterweger et al, 2016). In breaststroke swimmers, the men-to-women ratio remained unchanged for 50 m, 100 m and 200 m (Knechtle et al, 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…2 However, we have only very limited knowledge about the changes in performance in the last decades in age-group runners (ie, master runners older than 35 years) in track running. 3 In other sports disciplines such as pool swimming, master athletes increased participation and improved performance in freestyle, 4 breaststroke, 5 and backstroke 6 swimming. Interestingly, older women (ie, older than 80-90 years) were not slower than older men.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, older women (ie, older than 80-90 years) were not slower than older men. [4][5][6] Participation and performance trends in running were mainly investigated for marathon running where preferably large city marathons such as the "New York City Marathon" and other races of the "World Marathon Majors" were analyzed. 7,8 Several studies demonstrated that female and male master runners increased participation 7-10 and improved performance [7][8][9] in marathon running compared to younger age-groups.…”
Section: Introductionmentioning
confidence: 99%
“…Swimming races are mainly held as indoor pool competitions (18,30), but can also be held as openwater competitions. Open-water swimming, such as the 'English Channel Crossing', is of increasing popularity (8).…”
Section: Introductionmentioning
confidence: 99%